Pengaruh Gaya Kepemimpinan, Komunikasi, Disiplin Kerja dan Budaya Organisasi Terhadap Pada Kepuasan Kerja - Ramadhi, Ramadhi; Desi Rosalina; Eko Fikriando; Kiki Sarianti (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2022)
The purpose of this study was to determine the extent to which leadership style, communication, work discipline, and culture influence PT job satisfaction. Bina Thani Nusantara West Passaman. This study consists of her four independent variables:The only variables related to leadership style, communication, work discipline, organizational culture, and job satisfaction. Path analysis is used as an analysis method. The method of data collection in this study was through the use of questionnaires completed by the respondent, her PT staff. Bina Thani Nusantara West Passaman. Partial test (t-test) results: a) Leadership style has a large positive impact on job satisfaction b) Communication has a large positive impact on job satisfaction c) Job discipline has a large positive impact on job satisfaction d a) organizational culture has a positive impact on job satisfaction; e) management style, communication, work discipline, and organizational culture have a positive impact on job satisfaction